Siloxane-treated and copper-plasma-coated wood: Resistance to the blue stain fungus Aureobasidium pullulans and the termite Reticulitermes flavipes. (May 2017) - Gascón-Garrido, P.; Thévenon, M.F.; Mainusch, N.; Militz, H.; Viöl, W.; Mai, C.
Abstract: Scots pine ( Pinus sylvestris L.) sapwood specimens were subjected to a two-step treatment combining vacuum-pressure impregnation with short-chain siloxanes followed by copper deposition on the wood surface via atmospheric pressure plasma. The obtained materials were exposed to a blue stain fungus in a laboratory test following EN 152 (2011). Copper treatment alone reduced fungal colonisation, but did not fully prevent it. A two-step treatment was able to impart high resistance to Aureobasidium pullulans . Termite resistance of siloxane-treated and copper-plasma coated wood was also assessed. A laboratory no-choice test according to EN 118 (2013) revealed strong attack by Reticulitermes flavipes, but termite mortality increased compared to untreated wood. In contrast, under choice conditions, R. flavipes exhibited significant avoidance towards the treated specimens. Graphical abstract: Highlights: In a first-step: wood was vacuum-pressure impregnated with amino-siloxane emulsion. In a second-step: copper micro-particles were deposited on wood surface using plasma. The two-step treatment imparted high blue stain resistance to wood. Under no-choice conditions, the two-step treatment did not impart termite resistance. At choice of feeding, termites prefer untreated wood rather than treated wood.